Effectiveness of the policy to accelerate stunting reduction through convergence action for handling stunting In north sulawesi province - Lidya Hendrietta Tangel; Ika Sartika; Imelda Hutasoit (Sean Institute, 2024)
The problem of stunting is still homework for the North Sulawesi Provincial Government because currently the stunting rate in this province is still quite high. Public awareness of stunting is still low due to various reasons including distance and negligence. It is important to assess the effectiveness of policies to accelerate stunting reduction in North Sulawesi Province by seeing whether the efforts made are in line with the expected objectives, including the use of resources, infrastructure and the resulting impacts. Using qualitative research by studying in more depth and describing the data and facts that will be collected to answer the problem formulation. The results of data analysis and discussion have been carried out well but still have not reached the optimal level. This can be observed from several aspects of appropriate policy that are relevant and significant to ongoing issues, primarily focused on formulating policies that are appropriate to the nature of the problem to be solved, not apart from the role of the provincial government in coordinating, synergizing and evaluating the implementation of accelerating stunting reduction in an effective, convergent and integrated manner involving cross-sectors.